Multidimensional Statistical Analysis of Life Satisfaction of Older People; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Ivankina L. I. Lyubov Ivanovna; Mikhalchuk A. A. Aleksandr Alexandrovich; Arefiev V. P. Vladimir Petrovich; Filipenko N. M. Nikolai Maksimovich; Novoseltseva D. Darya (2017, 2017)
Title screen